A practical strategy to improve econometric modeling–a case study for informal economy on the Republic of Macedonia - Asani, Dashamir; Prenga, Dode (International Journal of Scientific Research and Management (IJSRM), 2018)
Here we consider some proposal-steps in the calculation of the shadow economy as a latent or simply response variable in the models that involve high volatile observable as the money aggregates etc., and if the number of data point is small. In this case we propose to check for possible extreme behavior or self-organization regimes present in the series by testing e log-periodic fit to the data. To improve the linear regressions critical points (if found) have been excluded from series by simply truncating them. Next, the presence of more general regimes is analyzed using empirical mode decomposition techniques, and we estimate that the best truncated series to be used should exclude the edges of such regimes. In the case of short term regimes, we propose to use series in intervals that include many cycles. This technique worked for the calculation of informal economy in the Republic of Macedonia for the short period of [2004, 2016] but it is supposed to improve calculation for other cases as well